A two-photon responsive hydroxyphenylquinazolinone (HPQ)-based fluorescent organic nanoprodrug for H2S release against oxidative stress. Issue 9 (11th January 2023) - Chaudhuri, Amrita; Singha, Tara; Jena, Bikash Chandra; Shee, Maniklal; Datta, Prasanta Kumar; Mandal, Mahitosh; Singh, N. D. Pradeep
Abstract : The development of an efficient two-photon responsive HPQ-based fluorescent organic nanoprodrug for H2 S release against oxidative stress. Abstract : Light-activated H2 S donors have attracted considerable interest in understanding the physiological role and clinical potential of H2 S, as their release is highly localized and controlled. Herein, we have evolved a new HPQ chromophore-based fluorescent organic nanosystem localized in a target area that tolerates oxidative stress and precisely releases H2 S under one- and two-photon irradiation with real-time monitoring capability. The two-photon absorption cross-section of this new phototrigger was calculated to be 283 GM at 720 nm. H2 S photorelease was also demonstrated in vitro on the MDA-MB-468 cell line in the presence of excess ROS. Our developed H2 S nanoprodrug can be applied to living systems to release the H2 S-gasotransmitter under laser irradiation in a phototherapeutic window.